Pedagogical Insights into the Perceptions and Attitudes of Pharmacy Students Toward Patient Safety: A Cross-Sectional Study from Pakistan - Samra Bashir; Akash Syed; Maryam Mahmood; Abdul Waheed Khan (Journal of Pedagogical and Teacher Professional Development, 2025)
The study evaluated pharmacy students’ perceptions and attitudes toward patient safety at two universities in Islamabad, Pakistan. Final-year Pharm D students completed a 21-item self-administered questionnaire. Data were analyzed using SPSS (version 23.0). The survey had a 97% response rate (160/165 students). Most students (95.7%) believed pharmacists should contribute to patient care, and 69.4% agreed they should report medication errors. Additionally, 87.5% supported incorporating patient safety education in university curricula. However, 63% perceived that competent healthcare professionals don’t make harmful errors, and 50% believed only medical practitioners can identify the cause of errors. Furthermore, 42.5% thought most errors occur due to factors beyond healthcare professionals’ control. The findings indicate that while pharmacy students in Pakistan have positive attitudes toward patient safety, some misconceptions highlight a knowledge gap. Thus, integrating standardized patient safety courses into the pharmacy curriculum is recommended.